Obesity Affects the Proliferative Potential of Equine Endometrial Progenitor Cells and Modulates Their Molecular Phenotype Associated with Mitochondrial Metabolism - Smieszek, Agnieszka; Marcinkowska, Klaudia; Pielok, Ariadna; Sikora, Mateusz; Valihrach, Lukas; Carnevale, Elaine; Marycz, Krzysztof (Cells, 2022)
The study aimed to investigate the influence of obesity on cellular features of equine endometrial progenitor cells (Eca EPCs), including viability, proliferation capacity, mitochondrial metabolism, and oxidative homeostasis. Eca EPCs derived from non-obese (non-OB) and obese (OB) mares were characterized by cellular phenotype and multipotency. Obesity-induced changes in the activity of Eca EPCs include the decline of their proliferative activity, clonogenic potential, mitochondrial metabolism, and enhanced oxidative stress. Eca EPCs isolated from obese mares were characterized by an increased occurrence of early apoptosis, loss of mitochondrial dynamics, and senescence-associated phenotype. Attenuated metabolism of Eca EPCs OB was related to increased expression of pro-apoptotic markers (CASP9, BAX, P53, P21), enhanced expression of OPN, PI3K, and AKT, simultaneously with decreased signaling stabilizing cellular homeostasis (including mitofusin, SIRT1, FOXP3). Obesity alters functional features and the self-renewal potential of endometrial progenitor cells. The impaired cytophysiology of progenitor cells from obese endometrium predicts lower regenerative capacity if used as autologous transplants.
Keywords: endoteliální progenitorové buňky; fenotyp; Phenotype; obesity; Obesity; endometrium; obezita; Endometrium; cellular metabolism; Stem Cells; Animals; ženské pohlaví; zvířata; koně; self-renewal potential; Endothelial Progenitor Cells; Female; endometrial progenitor cells; kmenové buňky; Horses